Analisis Beban Kerja Pada Pekerja Departemen Produksi Dengan Menggunakan Metode Full Time Equivalent (FTE) di PT Mulia Jaya Mandiri Balikpapan - Pratama, Alrazak Yudha; Andrianti, Irma; Syamtinningrum, Maeka Dita Puspa (Syntax Corporation, 2025)
HR plays a very important role in the success of an organization. To ensure that a job is achieved, the worker's workload should not exceed the worker's capacity to complete a job. Observations were carried out directly on 8 production worker sections carried out for three months at PT. Mulia Jaya Mandiri Balikpapan (PT. MJM) with 10 observations for 1 field of work in each type of production work. The results of the workload survey can be caused by the limited capacity of workers in processing their work or when processing information at PT. MJM, it was found that there were levels of workload experienced by workers, such as a worker who completed 2 jobs simultaneously with limited capacity. Based on the problems above, it is necessary to measure the workload of PT. MJM workers, where this can make the company's performance increase and reduce overtime working hours with the help of the Full Time Equivalent (FTE) method where the first step is to determine worker resources, determine cycle time, determine worker rating factor, determine allowance, calculate normal time and standard worker time, determine the FTE value and after that it is entered into the FTE assessment index the results obtained 2 jobs fall into the overload category, namely purchasing workers and casing rolling operator workers 1 with FTE values ​​​​of 1.29 and 1.39. It is known that the cause of the workload at PT. MJM, namely the lack of worker resources in the production section, due to the purchasing section, and the 2 Machine operator workers (Casing Threading) lacking worker resources coupled with the high consumer demand in November 2024 - January 2025. Recommendations for improvement by rearranging job descriptions for production workers and adding the number of competent and expert production worker resources in purchasing work and casing rolling machine operators, so that they can be more effective and efficient at PT. MJM